2022
DOI: 10.21098/bemp.v24i4.1766
|View full text |Cite
|
Sign up to set email alerts
|

What Drives Persistently High Inflationary Pressures in Vietnam? Some Evidence From the New Keynesian Curve Framework

Abstract: In this study, we revisit the inflation process in Vietnam through the New Keynesian Phillips Curve (NKPC) model. We use monthly and quarterly data frequencies to track the forces driving inflationary pressures up to a quarter. Interest rate, an important determinant of inflation, is often found to give theoretically inconsistent result. Hence, we examine different interest rates, including, the central bank policy rate, lending interest rate and one-month interbank interest rates. Further, there is no unified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The normalization of U.S. monetary policy is reflected in the tapering off, wherein the reference rate rises. The studies by (Antonakakis and Kizys, 2015); Kempa and Khan, 2017;Zhai and Morgan, 2016;Israel and Latsos, 2020;Klose, 2020;Maitra and Hossain, 2020;Nghiem and Narayan, 2021;Tiwari et al, 2019) reveal that the difference in interest rates between a developed country and a developing country causes a financial imbalance in the form of portfolio investment. Such a condition reverses capital flows into the developed nation, generating greater returns with minimal risk.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The normalization of U.S. monetary policy is reflected in the tapering off, wherein the reference rate rises. The studies by (Antonakakis and Kizys, 2015); Kempa and Khan, 2017;Zhai and Morgan, 2016;Israel and Latsos, 2020;Klose, 2020;Maitra and Hossain, 2020;Nghiem and Narayan, 2021;Tiwari et al, 2019) reveal that the difference in interest rates between a developed country and a developing country causes a financial imbalance in the form of portfolio investment. Such a condition reverses capital flows into the developed nation, generating greater returns with minimal risk.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It means the movement of both variables would continue in the long term. Nghiem and Narayan (2021) found that interest rate positively influences inflation. This is reversely expected.…”
Section: Introductionmentioning
confidence: 99%
“…2 This is what is often described in the literature as time-inconsistency of commitment to price stability (see Barro and Gordon, 1983) where the pledge is to discretion, rather than rules, in the operation of central banks. 3 A number of other studies have examined different dynamics of inflation although without CBI (See, Nghiem and Narayan, 2021;Rizvi and Sahminan, 2020;Narayan, 2019;Salisu, Ndako and Oloko, 2019;Salisu, Isah, Oyewole and Akanni, 2017;Bathaluddin and Waluyo, 2011) Monetary Fund, 1999;Berger et al, 2001;Bernhard et al, 2002;Klomp and de Haan, 2010;Hayo and Hefeker, 2010;Arnone and Romelli, 2013). Conversely, there is no such evidence of a general relationship between CBI and inflation in the case of developing economies (see Bagheri and Habibi, 1998;Meade, 2007, 2008;Desai et al, 2003;Bodea and Hicks, 2015;Garriga and Rodriguez, 2020).…”
Section: Introductionmentioning
confidence: 99%